Conceptual Framework of Mass Media Manipulative Models Forming - Puiu, Yulia Valerievna; Puiu, Daria Anatolevna; Sablin, Ilia Vladimirovich; Georgieva, Elena Savova; Bykov, Aleksey Yuryevich (International Review of Management and Marketing, 2015)
Nowadays mass media operate, transform and limit information thus becoming the main mechanism of influence in the modern society. State-of-the-art information technologies are used in order to increase the efficiency of government strategies. They help to turn the audience into an object of manipulation. Many theories studying mass media are focused on the influence the media has on its viewer or reader. Development of satellite television and some other media types that have almost unlimited coverage has increased the opportunities of cultural and information expansion. Mass media is extremely necessary during social development, because without its activity it is impossible to evaluate political consciousness, value system and purposes of all levels of the population and to gain public support of social changes. Nowadays there are two basic theoretical models of studying mass media political influence. The first one studies the influence of mass communications on individual behavior and social life in general. The second one has been developing for the last 30 years under the influence of cultural anthropology, structural theories, semiotics and other cross-disciplinary scientific fields. It was focused on perceiving the connections between “texts”, individuals and big social groups. In this article we study “influence studying” model and “text analysis” model. Keywords: mass media, manipulation, mediacracy, media theories. JEL Classifications: O38; Z13